Numerical simulation on spatial steering rule of directional perforation hydraulic fractures in low-permeability reservoir - Lu, Weiyong; Bai, Erhu; Wei, Le; He, Changchun; Sun, Yaohui; Shi, Lei (Frontiers in Earth Science, 2022)
For purpose of clearing the spatial pattern of hydraulic fracture during directional perforation in low-permeability unconventional reservoirs, RFPA2D-Flow software is used to numerically calculate their spatial steering trajectory and deflection distance The accuracy of numerical calculation results is verified by theoretical and experimental results. Then the influences of horizontal principal stress difference, perforation length and azimuth on the hydraulic fractures’ spatial steering trajectory are studied. It is shown by the results that: (1) the software can accurately predict the space steering trajectory and deflection distance of directional perforation hydraulic fractures. (2) Both deflection distance and spatial steering trajectory and of hydraulic fractures are quantitatively evaluation indexes, which are used to evaluate the hydraulic fractures’ spatial steering effects. (3) Under different horizontal principal stress differences, perforation azimuths and lengths, the same hydraulic fracture’s propagation trajectories are presented. They initiate from the perforation end, and gradually deflect along the maximum horizontal principal stress direction, and finally represent curved fractures like both wings. With the increase of horizontal principal stress difference, the fractures deflection distance decreases. However, it increases with the increase of perforation azimuth and length. Their deflection amplitude increases first and then decreases. Initiation pressure of hydraulic fracture rises with the decrease of perforation length and increase of perforation azimuth and horizontal principal stress difference.